APPLICATION OF ASSET REVALUATION BY THE PUBLIC ASSESSMENT OFFICE: A REFLECTION OF SHARIA ACCOUNTING, SHARI’AH ENTERPRISE THEORY - Musthafa, Tatang Fatah; Triyuwono, Iwan; Adib, Noval (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The purpose of this research is to have a deeper look at the practice of public appraisers at the Public Appraisal Services Office (KJPP) X, in carrying out the revaluation of fixed assets, mainly related to Islamic values by using Shari’ah Enterprise Theory. The research method used a qualitative approach with case study analysis techniques. The results of this study indicate that the scope of the KJPP assignment is still not in accordance with the Shari'ah Enterprise Theory